Ответы и объяснения

  • Katyuha85
  • почетный грамотей
2013-02-12T12:13:14+00:00

1).  (√34 + √46)² / (20 + √391) = (34+2*√34√46 +46) / (20 + √391) = (80 + 2*√(34*46)) / (20 + √391) = (80 +2*√1564) / (20 + √391) = (80 + 2*√(4*391)) / (20 + √391) = (80 + 2*2*√391) / (20 + √391) = (4(20+√391)) / (20 + √391) = 4

 

2). (15/8) * √(11ц1/5) : √(4ц3/8) = (15/8) * √(56/5) : √(35/8) = (15/8) * √(56/5 : 35/8) = (15/8) * √(56/5 * 8/35) =  (15/8) * √49 =  (15/8) * 7 = 105/8  = 13ц1/8

  • fuflunce
  • почетный грамотей
2013-02-12T12:22:36+00:00